2008
DOI: 10.1038/ncpneph0848
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous digitalis: pathophysiologic roles and therapeutic applications

Abstract: SUMMARYEndogenous digitalis-like factors, also called cardiotonic steroids, have been thought for nearly half a century to have important roles in health and disease. The endogenous cardiotonic steroids ouabain and marinobufagenin have been identified in humans, and an effector mechanism has been delineated by which these hormones signal through the sodium/potassium-transporting ATPase. These findings have increased interest in this field substantially. Although cardiotonic steroids were first considered impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 152 publications
2
103
0
2
Order By: Relevance
“…Our results, which show that Na,K-ATPase, the receptor of ouabain, stimulates dendritic growth in rat cortical neurons, support such a biological function for ouabain. Concentrations of endogenous ouabain in the embryonic human brain during the course of development are unknown but are predicted to lie in the subnanomolar-to-nanomolar range, as previously reported (13,32). Indeed, nanomolar concentrations of ouabain stimulates neurite outgrowth in human neuroblastoma cells (Fig.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our results, which show that Na,K-ATPase, the receptor of ouabain, stimulates dendritic growth in rat cortical neurons, support such a biological function for ouabain. Concentrations of endogenous ouabain in the embryonic human brain during the course of development are unknown but are predicted to lie in the subnanomolar-to-nanomolar range, as previously reported (13,32). Indeed, nanomolar concentrations of ouabain stimulates neurite outgrowth in human neuroblastoma cells (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Evidence indicates that circulating levels of ouabain and ouabain-like factors are elevated during pregnancy and in newborn infants (13,32), thereby suggesting a developmental role for this signaling molecule. Our results, which show that Na,K-ATPase, the receptor of ouabain, stimulates dendritic growth in rat cortical neurons, support such a biological function for ouabain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable evidence exists for the presence of endogenous ouabain-like molecules in mammalian tissues that may serve to regulate Na,K-ATPase activity (3,14,51). Particularly, a signaling role of the Na ϩ /K ϩ -ATPase has been demonstrated in regulating synaptic plasticity and dendritic growth in cortical neurons (52).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Previous studies have shown that EO is mostly produced in the adrenal cortex and circulating EO activate the sympathetic nervous system. 3,4 Their results suggested that these activations can be inhibited with b-blocker, angiotensin converting enzyme inhibitor and digoxin immune fab (antigen-binding fragments), Digi-Bind.…”
Section: Introductionmentioning
confidence: 99%